Perceptions of Religious Hypocrisy When Moral Claims Exceed Moral Action - Matthews, Mark A.; Mazzocco, Philip J. (2017)
In this study, we investigated perceptions of hypocrisy among Christian and non-Christian individuals. Specifically, participants (N = 121) were asked to evaluate people of different religious orientations in terms of perceptions of both claimed morality, actual behavior, and general hypocrisy. Across all designations, perceptions of moral hypocrisy were determined to be greater to the extent that moral claims exceeded actual behavior. Among non-Christian participants, perceptions of hypocrisy were highest with respect to devout and evangelical Christian targets. In contrast, among Christian participants, the highest ratings of hypocrisy were reserved for casual Christians (i.e., Christians who do not incorporate their faith into their daily life). Our findings have both theoretical implications regarding the nature of religious hypocrisy perceptions, as well as real-world implications for understanding inter-faith perceptions and interactions.